Power-time curve comparison between weightlifting derivatives - Suchomel, T. J.; Sole, C. J. (Journal of Sports Science & Medicine, 2017)
This study examined the power production differences between weightlifting derivatives through a comparison of power-time (P-t) curves. Thirteen resistance-trained males performed hang power clean (HPC), jump shrug (JS), and hang high pull (HHP) repetitions at relative loads of 30%, 45%, 65%, and 80% of their one repetition maximum (1RM) HPC. Relative peak power (PPRel), work (WRel), and P-t curves were compared. The JS produced greater PPRel than the HPC (p < 0.001, d = 2.53) and the HHP (p < 0.001, d = 2.14). In addition, the HHP PPRel was statistically greater than the HPC (p = 0.008, d = 0.80). Similarly, the JS produced greater WRel compared to the HPC (p < 0.001, d = 1.89) and HHP (p < 0.001, d = 1.42). Furthermore, HHP WRel was statistically greater than the HPC (p = 0.003, d = 0.73). The P-t profiles of each exercise were similar during the first 80-85% of the movement; however, during the final 15-20% of the movement the P-t profile of the JS was found to be greater than the HPC and HHP. The JS produced greater PPRel and WRel compared to the HPC and HHP with large effect size differences. The HHP produced greater PPRel and WRel than the HPC with moderate effect size differences. The JS and HHP produced markedly different P-t profiles in the final 15-20% of the movement compared to the HPC. Thus, these exercises may be superior methods of training to enhance PPRel. The greatest differences in PPRel between the JS and HHP and the HPC occurred at lighter loads, suggesting that loads of 30-45% 1RM HPC may provide the best training stimulus when using the JS and HHP. In contrast, loads ranging 65-80% 1RM HPC may provide an optimal stimulus for power production during the HPC.